Development of Digital Fiqh Books to Improve Learning Outcomes SMP IT As-Sunnah Makassar - Sulfah Muhtar; Pattaufi Pattaufi; Farida Febriati; Nurhikmah H (Himpunan Pengembang Kurikulum Indonesia, 2024)
Rapid advances greatly influence the world of education in technology, information, and communication. Teachers must be able to use technology to create innovative and effective learning. This research aims to identify the need for digital books, design the development of digital books, and measure the validity, practicality, and effectiveness of digital books. This research uses research and development methods focused on developing digital books. The development model refers to the ADDIE development model with five stages: analysis, design, development, implementation, and evaluation. The research was conducted at SMP IT As-Sunnah Makassar with 30 research students, 1 Fiqh subject teacher, and two validators. The digital book developed was declared very valid by media content/design experts and valid by material experts. The level of practicality was measured from questionnaire responses by teachers and students. Both assessments stated that it was convenient. The level of effectiveness of digital books is measured by pretest and posttest, which shows an increase in learning outcomes and that they are declared very effective. Based on the analysis results, it can be concluded that the development of digital fiqh books can be used in the learning process. Abstrak Dunia pendidikan sangat dipengaruhi oleh kemajuan pesat dalam teknologi, informasi dan komunikasi. Guru harus mampu menggunakan teknologi untuk membuat pembelajaran inovatif dan efektif. Penelitian ini bertujuan untuk mengidentifikasi kebutuhan buku digital, mendesain pengembangan buku digital dan mengukur tingkat validitas, kepraktisan, dan keefektifan buku digital. Penelitian ini menggunakan metode penelitian pengembangan (Research and Development) yang difokuskan untuk mengembangkan buku digital. Model pengembangan yang digunakan mengacu pada model pengembangan ADDIE dengan lima tahapan; analysis, design, development, implement, dan evaluate. Penelitian dilaksanakan di SMP IT As-Sunnah Makassar dengan penelitian 30 siswa, 1 orang guru mata pelajaran Fiqih, dan 2 orang validator. Buku digital yang dikembangkan dinyatakan sangat valid oleh ahli isi media/desain dan valid oleh ahli materi. Tingkat kepraktisannya diukur dari angket respon oleh guru dan siswa, dari kedua penilaian dinyatakan sangat praktis. Tingkat keefektifan buku digital diukur dengan pretest dan posttest yang menunjukkan terjadinya peningkatan hasil belajar sehingga dinyatakan sangat efektif. Berdasarkan hasil analisis dapat disimpulkan bahwa pengembangan buku digital fiqih dapat digunakan dalam proses pembelajaran. Kata Kunci: buku digital; fiqih; hasil belajar